2021
DOI: 10.1007/s11357-021-00375-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress programs a demasculinization of glutamatergic transmission in stress-related brain regions of aged rats

Abstract: Brain aging may be programmed by early-life stress. Aging affects males and females differently, but how perinatal stress (PRS) affects brain aging between sexes is unknown. We showed behavioral and neurobiological sex differences in non-stressed control rats that were strongly reduced or inverted in PRS rats. In particular, PRS decreased risk-taking behavior, spatial memory, exploratory behavior, and fine motor behavior in male aged rats. In contrast, female aged PRS rats displayed only increased risk-taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
(112 reference statements)
0
6
0
1
Order By: Relevance
“…This finding deserves further investigation because previous studies found that men had higher SARS-CoV-2 infectivity rates compared to women [39][40][41][42], and male participants with underlying conditions, including diabetes, hypertension, and cardiovascular diseases developed a severe form of the infection, with increased mortality rate [43,44]. Many factors such as hormone-specific reaction and activity of X-linked genes, which modulate the innate and adaptive immune response to virus infection were suggested [41,42,[45][46][47][48].…”
Section: Data Management and Statistical Analysismentioning
confidence: 90%
“…This finding deserves further investigation because previous studies found that men had higher SARS-CoV-2 infectivity rates compared to women [39][40][41][42], and male participants with underlying conditions, including diabetes, hypertension, and cardiovascular diseases developed a severe form of the infection, with increased mortality rate [43,44]. Many factors such as hormone-specific reaction and activity of X-linked genes, which modulate the innate and adaptive immune response to virus infection were suggested [41,42,[45][46][47][48].…”
Section: Data Management and Statistical Analysismentioning
confidence: 90%
“…Further, rodent models suggest perinatal stress exposure may lead to the demasculinization of the developing fetal brain, documenting decreased testosterone and increased estradiol levels in exposed males, but not females, further suggesting a role for endocrine disruptions following adversity exposure. 59 However, our understanding of these sex-specific processes remains limited. It is important to note whereas in the broader (i.e., non-infant neuroimaging) literature of intergenerational adversity there are a number of studies that have documented increased susceptibility in males, there are exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…During postnatal development, the NR2B is replaced by the NR2A receptor subunit. Excessive levels of glucocorticoids increase glutamate release [ 41 ], causing neurotoxicity, which increases apoptosis, as shown in the hippocampus and other brain regions during the first postpartum week in rats [ 42 , 43 ]. It has been shown, for example, that selective loss of the NR2B protein and subsequent synaptic dysfunction weaken the function of the prefrontal cortex during development and provoke the appearance of early cognitive impairments [ 44 ].…”
Section: Discussionmentioning
confidence: 99%